Graveyards as Sanctuaries: Exploring Right to the City Spaces in Arundhati Roy’s The Ministry of Utmost Happiness - Dangol , Bhabika (NPRC Journal of Multidisciplinary Research, 2025)
Background: Arundhati Roy’s The Ministry of Utmost Happiness (2017) examines urban spatiality by portraying marginalized characters navigating unjust constructs in city spaces such as Delhi and Kashmir. Method: Employing the urban spatial theory and right to the city concept developed by Marxist Sociologist Henri Lefebvre, this paper delves into the main characters, Anjum and Tilo, who become the leaders of their marginalized communities. Result: The complexities of contemporary India, characterized by a diverse population living under social injustice and political violence, persist in the growing urban space and fight for their right to city space. Conclusion: Marginalized communities show strong resistance and strive to prove their existence in the grand city spaces. The disregarded hubs mark their territory in the politically commercialized cities. Novelty: The paper promotes a nascent view of Roy’s spatial confrontation, which reinvents urbanity as a contested concept where previously disregarded existences regain visibility. This paper scrutinizes the city as a social and spatial product in prominent South Asian cities, such as Delhi.